Microbial Changes in Hand Skin During COVID-19: A Longitudinal Study in Majorca, Spain - Cristina Turpín; Antonio Doménech-Sánchez (Microbiology Research)
The COVID-19 pandemic prompted widespread adoption of intensified hand hygiene practices, raising concerns about their medium-term impact on the skin microbiome. This study investigates alterations in the hand microbiome of healthy adults during the pandemic compared to pre-pandemic periods in Majorca, Spain. A total of 30 volunteers (16 women, 14 men; mean age 44.1 ± 8.8 years) were sampled between 2014 and 2021. Palm swabs were collected following WHO guidelines, alongside measurements of skin pH, temperature, and handwashing frequency. Bacterial DNA was extracted and analyzed via 16S rRNA (V3-V4) metagenomic sequencing to assess microbial diversity and composition. Results revealed a significant decline in microbial diversity during the COVID-19 period, accompanied by a marked shift in the community structure. The Firmicutes phylum dominated, with Bacillales increasing from 30.7% to 84.1%, primarily driven by a surge in Staphylococcus species (e.g., S. pasteuri). Conversely, S. hominis and Actinomycetales nearly disappeared. No significant associations were observed with gender or handwashing frequency. The skin temperature increased during the pandemic, while the pH remained stable. The Staphylococcus/Bacillus ratio shifted significantly, favoring Staphylococcus dominance. These findings, derived from a geographically limited population in Majorca, Spain, demonstrate that stringent hygiene measures during COVID-19 reduced microbial diversity and restructured hand microbiome composition. The study underscores the necessity for balanced hygiene strategies that mitigate pathogen transmission while preserving beneficial microbial communities critical to skin health.